Peran Dan Pengelolaan Media Sosial Instagram @apilogy.id - Maharani, Azka Ayu; Ismail, Oki Ahmad (eProceedings of Management, 2024)
The current challenge for companies is introducing their products in the digital era. To address this challenge,APILOGY, a business product in the form of an API marketplace under PT Telekomunikasi Indonesia Tbk, optimallymanages its Instagram content. However, there are several obstacles in implementation, such as a lack of contentvariety and the inability to effectively manage content. Consequently, APILOGY recognizes the growing need forinformation by utilizing Instagram as a strategy to manage content. This design project employs several theories,including communication theory, AIDA (Attention, Interest, Desire, and Action), Instagram social media, Instagramcontent features, and content production. Primary data for this project was obtained through observation, interviews,and documentation. For secondary data, the authors conducted scientific studies through journals, websites, andcredible articles. The Instagram content management process for @apilogy.id was carried out over four months, fromSeptember to December 2023. This project design includes pre-production activities such as channel identification,content strategy, and audience identification; production activities including social media planning, scenarioconcepts, copywriting, content visualization, and tapping; and post-production activities such as review, revision,uploading, evaluation, and content analysis. Through these activities, the implementation of APILOGY's contentmanagement strategy aims to build public trust in the products and features provided by APILOGY. Keywords-AIDA, communication, content, Instagram social media.